The Persistence of White Privilege - Stephanie M. Wildman (Washington University Journal of Law & Policy, 2005)
Socio-cultural factors, such as societal practices and thinking patterns, including language itself, operate in conjunction with material forces to reinforce white privilege, enabling whites to self-perpetuate as a dominant racialized identity, albeit a transparent one. This Essay focuses on four of these socio-cultural factors: (1) the contemporary cultural push to colorblindness; (2) the sleight of mind that typifies the relation between an individual and groups in American culture; (3) a comfort zone in whiteness, which includes whiteness as the fabric of daily life for whites and white participation in the construction of race from a white-privileged viewpoint; and (4) the tendency for holders of white privilege to “take back the center” in discourse, turning attention away from potentially uncomfortable conversations about race toward an emphasis on white concerns and issues. These dynamics support the persistence of privilege.
Keywords: Critical race theory; Race preferences (Affirmative action)